PHARMACOLOGICAL EVALUATION OF ANTIDEPRESSANT ACTIVITY OF THE ETHANOLIC EXTRACT OF BOMBAX CEIBA FLOWERS IN ALBINO WISTAR RATS - Aarti Sati , Ankita Tomar, Deepti Negi, Suneha Rani , Priyanka Bhandari (Chelonian Research Foundation, 2024)
A significant segment of the worldwide population experiences depression, a prevalent mental health issue. Plant extracts are among all Organic compounds gained attention interest due to their possible antidepressant properties. The study's objective is to analyse whether an ethanolic extract of Bombax ceiba flowers exhibits antidepressant effects on Albino Wistar rats. Thirty Swiss Albino Wistar rats were divided into five groups, with each group containing six rats, and the study lasted for 42 days. We study three doses of the flower extract of B. ceiba (100, 200, 400mg/kg) the effects of both acute and chronic depression were evaluated using two models: the Porsolt forced swim test and the tail suspension test. In the acute trial, drugs (test drug, standard control, and vehicle) were given orally one hour prior to the experiment, and in the chronic research, the drugs were given daily for 14 days. The force swim test and tail suspension test were used in both acute and chronic investigations to show that imipramine had strong antidepressant action. This was evidenced by a decrease in the period of immobility. B. ceiba had antidepressant effect that was dose dependant. The antidepressant effect of B. ceiba 100 mg/kg was only evident in the acute force swim test. In the force swim test (both acute and chronic), B. ceiba 200 mg/kg showed antidepressant action; however, it did not show any effect in the tail suspension test. In investigations conducted on both acute and chronic patients, B. ceiba 400 mg/kg demonstrated maximum antidepressant effect that was comparable to that of imipramine, a prescription medication. B. ceiba showed dose dependent antidepressant action with BC-400mg/kg showing maximum effect.